2014
DOI: 10.2169/internalmedicine.53.2996
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Findings of a Cerebrotendinous Xanthomatosis Patient with a Novel p.A335V Mutation in the <i>CYP27A1</i> Gene

Abstract: We herein describe the case of a Japanese cerebrotendinous xanthomatosis (CTX) patient with a novel CYP27A1 gene mutation. The patient had been diagnosed with cataracts at 25 years of age and subsequently developed neurological symptoms in his forties, being referred to our hospital at 47 years of age. Upon admission, Achilles tendon xanthomas, cognitive impairment, dysphagia, dysarthria, dystonia, spasticity, muscle weakness and ataxia were observed. Brain MRI revealed abnormal signals in the dentate nuclei, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…8 The other four families were compound heterozygous and all patients showed classic form CTX phenotype. [8][9][10][11] Similar to the p.R405Q mutation, all mutations observed in spinal form CTX were also found in classic form CTX, indicating that none of these mutations is preferentially associated with either the classic or spinal form of the disease. 3,4 Although CTX can mimic neurodegenerative diseases, such as spastic paraplegia and spinocerebellar degeneration, early diagnosis of CTX is crucial because treatment with CDCA reverses metabolic derangement and can prevent or even improve neurological dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The other four families were compound heterozygous and all patients showed classic form CTX phenotype. [8][9][10][11] Similar to the p.R405Q mutation, all mutations observed in spinal form CTX were also found in classic form CTX, indicating that none of these mutations is preferentially associated with either the classic or spinal form of the disease. 3,4 Although CTX can mimic neurodegenerative diseases, such as spastic paraplegia and spinocerebellar degeneration, early diagnosis of CTX is crucial because treatment with CDCA reverses metabolic derangement and can prevent or even improve neurological dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…8 The p.R405Q mutation was reported previously in five CTX families. [8][9][10][11] Chen et al reported a Japanese family homozygous for p.R405Q mutation, who showed typical CTX manifestations, including tendon xanthomas, cataracts, neurological dysfunctions, elevated serum cholestanol level, and undetectable sterol 27-hydroxylase activities. 8 The other four families were compound heterozygous and all patients showed classic form CTX phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…4b ). p.R405Q in CYP27A1 had previously been reported in three siblings with CTX [ 7 ], and in several Japanese CTX patients [ 5 , 8 ]. p.Q85R had previously been reported as the first mutation identified in all variations of CTX.…”
Section: Case Presentationmentioning
confidence: 93%
“…Magnetic resonance imaging (MRI) studies show decreases in total brain volume (particularly gray matter) (Guerrera et al 2010), cerebral and cerebellar atrophy (Pilo de la Fuente et al 2008;Berginer et al 1994), extensive white mater lesions of the spinal cord (in patients with spinal xanthomatosis) (Verrips et al 1999a;Yanagihashi et al 2016), and bilateral hyperintensity of the dentate nuclei and surrounding white matter (considered characteristic of CTX; Fig. 3) (De Stefano et al 2001;Guerrera et al 2010;Yoshinaga et al 2014). Increased peaks of choline on MR spectroscopy (MRS) have also been observed and may be useful to monitor response to therapy (Degos et al 2016); abnormal lipid peaks have also been detected on MRS, although their clinical significance is uncertain (Embirucu et al 2010).…”
Section: Diagnosis and Testingmentioning
confidence: 99%